Os 100 artigos mais citados sobre o uso de agregados plaquetários em odontologia: um estudo bibliométrico - Carolina Veríssimo Lacerda (2022)
The regenerative potential and the improvement in the clinical course of tissue healing has generated great interest in Dentistry and many articles have been published in this sense. Bibliometric analysis is useful in determining the most influential studies in specific fields. The present bibliometric study aimed to identify and analyse the 100 most cited papers on the use of platelet aggregates in Dentistry. An electronic search with a set of pre-tested keywords was performed using the Web de Science Core Collection (WoS- CC) without any language restriction, study design or year of publication. Out of a total of 4664 identified publications, the top 100 were included based on their citation count. After full- text reading, respective bibliometric data including publication title, authorship, citation count, current 2022 citation index, citation density, year of publication, country and institution of origin, journal of publication, platelet aggregate types, study design, level of evidence, and keywords were extracted and analyzed. Analysis and visualization of selected documents and related data were performed using software including MS Excel and VOS viewer. The VOS Viewer was used to generate graphical representations of the data. In addition, network graphs were generated to assess the various associations between research topics, countries, organizations, authors, journals and citations. The 100 most cited articles on platelet aggregates in Dentistry received a total of 17,184 citations (mean: 171.84; minimum: 97; maximum: 934) in WoS-CC. Most articles were published between 2000 and 2019 (n = 99), the oldest (Preparation and use of fibrin glue in surgery) being published in the journal Biomaterials 1995, vol. 16 no. 12 by Silver et al, with 109 citations in WoS-CC. Europe was the continent that had the highest number of publications (47 articles; 9,532 total citations), and the United States was the country that had the highest number of publications (23 articles; 2,466 total citations). The Journal of Periodontology was the one that published the higher number of researches in this field (13 articles; 2,183 citations). The research center with the highest number of citations was the Nagoya University Graduate School of Medicine, located in Japan, representing 7% of publications (805 citations). Clinical trials were the most present study design (41 articles; 6,102 citations). The identification of the 100 most cited studies on platelet aggregates through bibliometric analysis allowed the observation of collaborative networks, with a predominance of citations for clinical trials and review articles, with emphasis on studies with authors from Europe, with Italy in its predominance within from the mainland. Of the 100 most cited articles, there is a domain of PRP studies, with authors from the United States with the highest number of publications. Taken together, the findings provided an amplified view regarding the publication dynamics of studies in the area.